2018
DOI: 10.1007/s00586-018-5571-7
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic anterior stabilization for thoracolumbar fractures in patients without spinal cord injury: quality of life and long-term results

Abstract: Purpose To determine the health-related quality of life (QOL), safety and radiologic parameters after thoracoscopic treatment of traumatic thoracolumbar fractures using a distractible cage in patients without spinal cord injury (SCI). Methods Retrospective cohort study of patients treated between 2004 and 2012 in a university level-one trauma center. Patient and treatment characteristics were collected from the hospital information system. All available radiographic material was assessed for fracture character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
2
4
1
3
Order By: Relevance
“…The main disadvantages of the open approach are the relatively high complication rates and post-thoracotomy pain syndrome, which can develop in up to 31 % of cases [57,58]. In many hospitals over recent years, minimally invasive thoracoscopic stabilisation has therefore established itself and significantly reduced access morbidity [59]. Alternatively, anterior stabilisation, e.g.…”
Section: Exclusively Anterior Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The main disadvantages of the open approach are the relatively high complication rates and post-thoracotomy pain syndrome, which can develop in up to 31 % of cases [57,58]. In many hospitals over recent years, minimally invasive thoracoscopic stabilisation has therefore established itself and significantly reduced access morbidity [59]. Alternatively, anterior stabilisation, e.g.…”
Section: Exclusively Anterior Proceduresmentioning
confidence: 99%
“…In den letzten Jahren hat sich dementsprechend in vielen Kliniken die minimalinvasive bzw. thorakoskopische Stabilisation durchgesetzt, welche die Zugangsmorbidität deutlich verringert [59]. Alternativ kann die ventrale Stabilisation z.…”
Section: Pedikelschraubenimplantation Und -Dimensionunclassified
“…Recently, Smits et al [10] reported promising results in 46 patients with thoracolumbar fractures treated by MIAS at a median follow-up of 49 months. Thereby, the overall bisegmental loss of reduction in this cohort was comparable to our results with a mean of 6.8°.…”
Section: Radiologic Outcomementioning
confidence: 99%
“…In 2013, Spiegl et al [9] reported predominantly promising 6-year results and a low complication rate in patients with incomplete thoracolumbar burst fractures. Smits et al [10] published promising long-term results in 46 patients treated by MIAS. Notably, the overall spinal alignment was not evaluated although this is suggested to represent an important prognostic parameter [11] for long-term success of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…В последние несколько десятилетий отмечается практически тотальная экспансия методов торакоскопической хирургии при лечении многих заболеваний и травмы органов груди [1,2,3]. При этом эволюция хирургических доступов для проведения торакоскопии движется в направлении от классических -многопортовых -до однопортовых операций и простирается далее в сторону использования нестандартных доступов [4,5].…”
Section: Introductionunclassified